Quantum chemical calculation study on the thermal decomposition of electrolyte during lithium-ion battery thermal runaway - Tian, Yao; Zhao, Yun; Kang, Yuqiong; Wu, Junru; Meng, Yuefeng; Hu, Xia; Huang, Ming; Lan, Bo; Kang, Feiyu; Li, Baohua (Frontiers in Energy Research, 2024)
Understanding the behavior of lithium-ion battery electrolytes during thermal runaway is essential for designing safer batteries. However, current reports on electrolyte decomposition behaviors often focus on reactions with electrode materials. Herein we use quantum chemical calculations to develop a model for the thermal decomposition mechanism of electrolytes under both electrolyte and ambient atmosphere conditions. The thermal stability is found to be associated with the dielectric constants of electrolyte constituents. Within the electrolyte, the solvation effects between molecules increase electrolyte stability, making thermal decomposition a more difficult process. Furthermore, Li+ is observed to facilitate electrolyte thermal decomposition, as the energy required for the thermal decomposition reactions of molecules decreases when they are bonded with Li+. It is hoped that this study will offer a theoretical basis for understanding the complex reactions occurring during thermal runaway events.